ISOLATION AND IDENTIFICATION OF BACTERIA STAPHYLOCOCCUS AUREUS FROM DIFFERENT PATHOLOGICAL SAMPLES (Academicia Globe: Inderscience Research, 2023)
This study was conducted to investigate staphylococcal bacteria from pathological samples collected from Imam Al- Sadiq Hospital and Al-Sadr Teaching Hospital during the period from October 2022 to March 2023, where 10 samples were collected that can be considered as control samples for comparison with pathological samples, and 55 pathological samples from both sexes ( male and female), Where the percentage of females in the samples under study was more than that of males, where the number of female samples was 31 samples with a rate of (56.4%) and the number of male samples was 24 samples with a rate of (43.6%) and of different ages, where the most diseased samples were of age (21-30) years with a number of samples of 15 (27%) and the least samples in Age (71-80) years, with 1 sample and a rate of (2%), The bacteria studied in the research were collected from different pathological sites, and the results showed that the highest number of samples was 55 from boils and acne with a percentage of (46%), and the lowest number of samples from wounds was 2 samples and a rate of( 3%). The bacteria isolated from pathological samples were diagnosed through phenotypic, microscopic and biochemical tests.